Efficient and safe glycaemic control with basal‐bolus insulin therapy during fasting periods in hospitalized patients with type 2 diabetes using decision support technology: A post hoc analysis. Issue 9 (22nd June 2021) - Hochfellner, Daniel A.; Rainer, Raphael; Ziko, Haris; Aberer, Felix; Simic, Amra; Lichtenegger, Katharina M.; Beck, Peter; Donsa, Klaus; Pieber, Thomas R.; Fruhwald, Friedrich M.; Rosenkranz, Alexander R.; Kamolz, Lars‐Peter; et al.
Abstract: Aim: To evaluate the efficacy and safety of basal‐bolus insulin therapy in managing glycaemia during fasting periods in hospitalized patients with type 2 diabetes. Materials and Methods: We performed a post hoc analysis of two prospective, uncontrolled interventional trials that applied electronic decision support system‐guided basal‐bolus (meal‐related and correction) insulin therapy. We searched for fasting periods (invasive or diagnostic procedures, medical condition) during inpatient stays. In a mixed model analysis, patientsʼ glucose levels and insulin doses on days with regular food intake were compared with days with fasting periods. Results: Out of 249 patients, 115 patients (33.9% female, age 68.3 ± 10.3 years, diabetes duration 15.1 ± 10.9 years, body mass index 30.1 ± 5.4 kg/m 2, HbA1c 69 ± 20 mmol/mol) had 194 days with fasting periods. Mean daily blood glucose (BG) was lower (modelled difference [ModDiff]: −0.5 ± 0.2 mmol/L, P  = .006), and the proportion of glucose values within the target range (3.9‐10.0 mmol/L) increased on days with fasting periods compared with days with regular food intake (ModDiff: +0.06 ± 0.02, P  = .005). Glycaemic control on fasting days was driven by a reduction in daily bolus insulin doses (ModDiff: −11.0 ± 0.9 IU, P  < .001), while basal insulin was similar (ModDiff: −1.1 ± 0.6 IU, P  = .082) compared with non‐fasting days. Regarding hypoglycaemic events (BG < 3.9 mmol/L), there was no difference between fasting and non‐fasting days ( χ 2 0.9% vs. 1.7%, P  = .174). Conclusions: When using well‐titrated basal‐bolus insulin therapy in hospitalized patients with type 2 diabetes, the basal insulin dose does not require adjustment during fasting periods to achieve safe glycaemic control, provided meal‐related bolus insulin is omitted and correction bolus insulin is tailored to glucose levels.